2008
DOI: 10.1073/pnas.0801353105
|View full text |Cite
|
Sign up to set email alerts
|

Structure of tumor suppressor p53 and its intrinsically disordered N-terminal transactivation domain

Abstract: Proteins with intrinsically disordered domains are implicated in a vast range of biological processes, especially in cell signaling and regulation. Having solved the quaternary structure of the folded domains in the tumor suppressor p53 by a multidisciplinary approach, we have now determined the average ensemble structure of the intrinsically disordered N-terminal transactivation domain (TAD) by using residual dipolar couplings (RDCs) from NMR spectroscopy and small-angle x-ray scattering (SAXS). Remarkably, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
413
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 380 publications
(438 citation statements)
references
References 51 publications
24
413
0
1
Order By: Relevance
“…S1); however, their arrangement in the full-length protein has been a subject of controversy, and alternative models of quaternary structural arrangement have been postulated. One model of the human protein obtained from electron microscopy and small-angle X-ray scattering (SAXS) is consistent with structural studies on the isolated TET domain whereby the full-length tetramer and truncated constructs associate via the TET domain (4)(5)(6). But in a model of the murine protein, it is proposed that oligomerization occurs via contacts between N and C termini of the protein, as well as the core domains, and the subunits of the TET domain do not oligomerize (7,8).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…S1); however, their arrangement in the full-length protein has been a subject of controversy, and alternative models of quaternary structural arrangement have been postulated. One model of the human protein obtained from electron microscopy and small-angle X-ray scattering (SAXS) is consistent with structural studies on the isolated TET domain whereby the full-length tetramer and truncated constructs associate via the TET domain (4)(5)(6). But in a model of the murine protein, it is proposed that oligomerization occurs via contacts between N and C termini of the protein, as well as the core domains, and the subunits of the TET domain do not oligomerize (7,8).…”
mentioning
confidence: 68%
“…Proteins were expressed as His-lipoyl domain fusions [full-length p53, p53C (94-296) and (89-296), TET L348A (325-355), p53 TAD-PRR-C (1-312), p53C-TET (96-355), and alanine point mutants of the proteins] were purified by combination of Ni 2þ -, heparin-affinity, and gel-filtration chromatography (6,22,27,36). Briefly: Cell lysis was performed using high-pressure homogenizer in a lysis buffer containing 25 mM K-phosphate, 300 mM NaCl, 10 mM imidazole, 5 mM β-mercaptoethanol, pH ¼ 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…Resonance assignments for WT human p53TAD were previously reported 12 and Bruker 750 MHz spectrometers equipped with pulse field Z-axis gradient cold probes, in 50 mM sodium phosphate buffer, 100 NaCl, 1 mM EDTA, 0.02% sodium azide and 2 mM DTT, at pH 6.8 (10% D 2 O). For HNCA and HNCACB experiments, data were acquired in 1 H, 13 C and 15 N dimensions using sweep widths of 13,020.8 (t 3 ) × 6,032.7 (t 2 ) × 3,000 (t 1 ) Hz and 1,024 (t 3 ) × 128 (t 2 ) × 32 (t 1 ) complex data points. The sweep widths and complex points for 2D HSQC experiments were 9,689.9 (t 2 ) × 2,500 (t 1 ) Hz and 1,024 (t All NMR spectra were processed with nmrPipe and analyzed in nmrView 26 .…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…In its free form, p53TAD exists in equilibrium between disordered and partially helical conformations [11][12][13] , whereas residues 19-25 form a stable amphipathic α-helix in the Mdm2 complex 14 (Fig. 1a).…”
mentioning
confidence: 99%
“…From a thermodynamic perspective, it has been suggested that destabilization of the native protein structure, leading to its unfolding, lowers the affinity of a protein for its ligand, without necessarily abolishing specificity (4)(5)(6). Furthermore, the highly dynamic nature of IDPs was suggested to promote alternative binding of the same disordered segments to different partners, the so-called "moonlighting effect" (7,8), increasing the repertoire of activities. An interesting mechanistic model, proposed by Wolynes and coworkers (9), suggests that the IDPs display an increased capture radius to recruit and bind partners.…”
mentioning
confidence: 99%